Plant pompom hard carbon composite negative electrode material and preparation method and application thereof

By compounding the plant velvet balls and other chemicals and sintering processes, prepare a hard carbon composite negative material with high ratio and conductivity, solve the problem of insufficient existing material performance, significantly improved its lithium ion battery in the lithium ion battery Waiting for the performance in the application.

CN114628655BActive Publication Date: 2025-01-28GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210189980.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-28
Publication Date
2025-01-28
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

The existing hard carbon composite anode materials have low theoretical capacity and energy density and few active sites, which limit their applications in lithium-ion batteries, supercapacitors and electrocatalysis.

Method used

Plant velvet balls are used as hard carbon precursors. Through the composite treatment of oxidant, lithium source, decentralizers, and carboxyl -containing lithium salt, it is prepared to prepare hard carbon composite materials with rich pores and high -ratio surface areas. This material improves its electrical and electrochemical performance through lithium -alkali oxidation and sintering process.

Benefits of technology

The ratio and first effect of hard carbon composite negative materials have been improved, the performance in lithium ion batteries and other energy storage equipment is improved, and the problem of insufficient traditional materials performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114628655B_ABST
    Figure CN114628655B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials, and discloses a plant pompom hard carbon composite negative electrode material and its preparation method and application. The hard carbon composite negative electrode material comprises the following raw materials: plant pompom, oxidant, lithium source, dispersant and carboxyl-containing lithium salt; the lithium source is at least one of LiAlO2, Li2SiO3 and LiSnO2. The three-dimensional micron structure of the hard carbon composite negative electrode material prepared by the present invention has abundant pores, which improves the specific surface area and conductivity of the hard carbon composite negative electrode material; the introduction of heteroatom materials such as N and O into the carbon of the hard carbon composite negative electrode material can also improve its electrochemical performance. Since N atoms and C atoms have similar electronic arrangements, the C element in the carbon skeleton is more easily replaced by N atoms, thereby changing the surface functional groups of the carbon material to improve its electrochemical performance, that is, improving the specific capacity and first efficiency of the hard carbon composite negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a plant pompom hard carbon composite negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have attracted widespread attention due to their high energy density, long service life, and good environmental compatibility. However, with the large-scale development of portable electronic products, electric vehicles, and renewable power stations, lithium battery materials with higher voltage, higher energy density, and superior rate performance are required, while improving cost, cycle life, and safety. In order to alleviate the pressure of mineral resource exploration, hard carbon electrode materials with lithium storage capacity similar to graphite have attracted people's attention. Hard carbon obtained from plant sources, such as sugarcane stalks, cotton, pine nut shells, peanut shells, and rice husks, which are abundant and low-cost raw materials, have also attracted people's attention as precursors of hard carbon. They have significant advantages such as wide sources, huge output, green preparation, renewable, excellent mechanical properties, and multiple modification sites. Developing potential hard carbon precursors is conducive to promoting the exploration of large-scale production of environmentally friendly and low-cost lithium-ion battery negative electrode materials.

[0003] Hard carbon materials are widely used in fields such as energy storage and conversion, but traditional hard carbon composite negative electrode materials have low theoretical capacity and energy density, few active sites, and low reversible capacity, which limits their application in lithium-ion batteries, supercapacitors and electrocatalysis. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a plant pompom hard carbon composite negative electrode material and a preparation method and application thereof. The prepared plant pompom hard carbon composite negative electrode material has abundant pores in its three-dimensional micron structure, which improves the specific surface area and conductivity of the plant pompom hard carbon composite negative electrode material.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A hard carbon composite negative electrode material comprises the following raw materials: plant pompoms, an oxidant, a lithium source, a dispersant and a carboxyl-containing lithium salt; the lithium source is at least one of LiAlO2, Li2SiO3 and LiSnO2.

[0007] Preferably, the dispersant is one of aminomethyltrimethylsilane solution and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0008] Further preferably, the dispersant is aminomethyltrimethylsilane solution.

[0009] Preferably, the oxidant is LiClO.

[0010] Preferably, the plant pompom is at least one of gentiana macrophylla, dandelion, rudbeckia oleracea, and ageratum.

[0011] Preferably, the carboxyl-containing lithium salt is lithium acetate.

[0012] Preferably, the specific surface area of ​​the hard carbon composite negative electrode material is 10-15m 2 / g.

[0013] Further preferably, the specific surface area of ​​the hard carbon composite negative electrode material is 11-14 m 2 / g.

[0014] Preferably, the lithium removal specific capacity of the hard carbon composite negative electrode material is 330.5-340 mAh g -1 ; The initial efficacy is 71-76%.

[0015] A method for preparing a hard carbon composite negative electrode material comprises the following steps:

[0016] (1) mixing plant pompoms and a dispersant, and then homogenizing to obtain a homogenous pompom filament liquid;

[0017] (2) mixing the homogeneous pompom filament liquid, an oxidant, a lithium source and an alkali solution, performing a lithium-alkali oxidation treatment, adding a carboxyl-containing lithium salt, performing a grafting reaction, stirring and layering, separating, and taking the upper suspended matter to obtain a pompom filament hydrogel;

[0018] (3) Drying the pompom filament hydrogel, performing a primary sintering, raising the temperature, and performing a secondary sintering to obtain a hard carbon composite negative electrode material.

[0019] Preferably, in step (1), the plant pompom is at least one of Ligusticum chuanxiong, Taraxacum officinale, Artemisia selengensis or Ageratum conyzoides.

[0020] Preferably, in step (1), the plant pompoms are dried before being mixed with the dispersant, and the drying temperature is 80° C.-100° C.; the drying atmosphere is a nitrogen atmosphere.

[0021] Preferably, in step (1), the dispersant is one of aminomethyltrimethylsilane solution and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0022] Further preferably, the dispersant is aminomethyltrimethylsilane solution.

[0023] Further preferably, the mass concentration of the aminomethyltrimethylsilane solution is 0.001-0.2 wt %.

[0024] Preferably, in step (1), the solid-to-liquid ratio of the plant pompom and the dispersant is (1-10) g:100 mL.

[0025] Preferably, in step (1), the specific step of the homogenization treatment is: subjecting the homogenized pompom liquid obtained by mixing the plant pompoms and the dispersant to shear treatment to obtain a homogenized pompom filament liquid.

[0026] Further preferably, the gap of the shearing groove is less than 50 μm, and the shearing time is controlled within 5-30 min.

[0027] Preferably, in step (1), the diameter of the filaments in the homogenized floc filament liquid is less than 10 μm.

[0028] Preferably, in step (2), the oxidant is LiClO.

[0029] Further preferably, the amount of LiClO added is 0.5-3wt% of the quality pompom filaments.

[0030] Preferably, in step (2), the lithium source is at least one of LiAlO2, Li2SiO3, and LiSnO2.

[0031] Preferably, in step (2), the alkali solution is LiOH solution.

[0032] Preferably, in step (2), the pH of the lithium alkali oxidation treatment is 9-14, the time of the lithium alkali oxidation treatment is 2-6 hours, and the temperature of the lithium alkali oxidation treatment is room temperature.

[0033] Preferably, in step (2), the Li content of the lithium alkali oxidation treatment is 0.0001-0.08 mol / L.

[0034] Preferably, in step (2), the carboxyl-containing lithium salt is lithium acetate.

[0035] Preferably, in step (3), the drying temperature is 60-90° C. and the drying time is 4-12 h.

[0036] Preferably, in step (3), the primary sintering temperature is 400-500° C., and the primary sintering time is 2-6 hours.

[0037] Preferably, in step (3), the primary sintering atmosphere is one of argon, nitrogen and neon.

[0038] Preferably, in step (3), the secondary sintering temperature is 500-1200° C., and the secondary sintering time is 2-6 hours.

[0039] Preferably, in step (3), the atmosphere for the secondary sintering is one of argon, nitrogen and neon.

[0040] Preferably, in step (3), the gas flow rate of the secondary sintering is 10-50 mL / min.

[0041] Preferably, in step (3), the length of the hard carbon composite negative electrode material is less than 20 μm.

[0042] The present invention also provides the use of the hard carbon composite negative electrode material in the preparation of batteries, catalysts and supercapacitors.

[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0044] (1) The three-dimensional microstructure of the hard carbon composite negative electrode material prepared by the present invention has abundant pores, which increases the specific surface area of ​​the hard carbon composite negative electrode material; the introduction of heteroatom materials such as N and O into the carbon of the hard carbon composite negative electrode material can also improve its electrochemical performance. Since N atoms and C atoms have similar electronic arrangements, the C elements in the carbon skeleton are more easily replaced by N atoms, thereby changing the surface functional groups of the carbon material to improve its electrochemical performance, that is, improving the specific capacity and initial efficiency of the hard carbon composite negative electrode material.

[0045] (2) The present invention first mixes the dispersant and the plant pompoms. Since the dispersant contains aminomethyltrimethylsilane, the pompoms can be evenly dispersed in the solution. In addition, the silane groups on the aminomethyltrimethylsilane can gradually replace the hydroxyl groups on the surface of the pompoms under stirring. The silane groups are reactive to inorganic ions and have better inorganic ion binding performance, thereby enhancing the ability to subsequently adsorb metal ions. Then, an oxidant, a lithium source and an alkali solution are added to perform lithium alkali oxidation treatment. Under the oxidation of the oxidant, various functional groups of the pompom filaments are gradually exposed. After adding alkali, a multi-group cross-linking reaction is carried out with the hydroxyl groups to further expose more functional groups. This process repeats itself, and the oxygen-containing active sites increase, which is beneficial to the subsequent grafting reaction of the pompom filaments with the loosened cross-linked network, so that the pompom filaments adsorb more AlO2 - Finally, through sintering, the specific capacity and initial efficiency of the hard carbon composite negative electrode material are improved, and the electrochemical performance is greatly improved.

[0046] (3) In the process of lithium alkali oxidation treatment by adding lithium source and alkali solution, since the lithium source contains LiAlO2, after sintering, the flannel filaments absorb more AlO2. - , can improve the specific capacity and initial efficiency of hard carbon composite negative electrode materials. The lithium source also contains Li2SiO3 and LiSnO2. After sintering, the wool ball filaments adsorb SiO3 2+ / SnO2 - The theoretical capacity of Si / Sn is higher than that of hard carbon. By reasonably combining Si / Sn with pompom hard carbon, the energy density of pompom hard carbon composite negative electrode materials is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a SEM image of the hard carbon composite negative electrode material prepared in Example 1 of the present invention;

[0048] Figure 2 This is the XRD diagram of the hard carbon composite negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0049] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0050] Example 1

[0051] The method for preparing the hard carbon composite negative electrode material of this embodiment comprises the following steps:

[0052] (1) Plant pompons were placed in a nitrogen atmosphere and dried at 85°C for 3.5 h. The dried pompons were mixed with 0.023 wt% aminomethyltrimethylsilane solution at a solid-liquid ratio of 1.2 g:100 mL to obtain a homogeneous pompon liquid. The homogeneous pompon liquid was sheared and filamented 6 times (each treatment time was 16 min) to obtain a homogeneous pompon filament liquid (filament diameter <10 μm).

[0053] (2) The homogeneous pompom filament liquid is mixed with LiClO (the amount of LiClO added is 0.71wt% of the homogeneous pompom filaments), and a LiAlO2+LiOH mixture (wherein the Li content is 0.027mol / L) is added for lithium alkali oxidation treatment for 3.5h (pH is 10.3) to obtain an oxidized homogeneous pompom filament liquid. The oxidized homogeneous pompom filament liquid is sent to a blender, 0.35g of lithium acetate is added to the blender, stirred, layered, separated, and the upper layer of suspended matter is taken to obtain a pompom filament hydrogel.

[0054] (3) The pompom filament hydrogel was vacuum dried at 65°C for 6.5 h to obtain pompom filaments, which were then placed in a nitrogen atmosphere (flow rate of 12 mL / min) and sintered at 462°C for 3 h. The temperature was then raised to 823°C for a second sintering for 3.6 h. The filaments were then cooled, washed, dried, and ultrasonically crushed to obtain a hard carbon composite negative electrode material.

[0055] Figure 1 is a SEM image of the hard carbon composite negative electrode material prepared in Example 1 of the present invention; Figure 1It can be seen that the diameter of the pompom filaments is between 0.1 and 4 microns, the material diameter concentration is good, and the consistency of the material morphology is good.

[0056] Figure 2 is the XRD pattern of the hard carbon composite negative electrode material prepared in Example 1 of the present invention; Figure 2 It can be seen that the prepared material has two diffraction peaks and the interlayer spacing is large, indicating that the prepared material is a composite material.

[0057] Example 2

[0058] The method for preparing the hard carbon composite negative electrode material of this embodiment comprises the following steps:

[0059] (1) The plant pompons were placed in a nitrogen atmosphere and dried at 85°C for 3.5 h. The dried pompons were mixed with 0.0654 wt% aminomethyltrimethylsilane solution at a solid-liquid ratio of 2.8 g:100 mL to obtain a homogeneous pompon liquid. The homogeneous pompon liquid was sheared and filamented 6 times (each treatment time was 16 min) to obtain a homogeneous pompon filament liquid (filament diameter <10 μm).

[0060] (2) The homogeneous pompom filament liquid is mixed with LiClO (the amount of LiClO added is 0.86wt% of the homogeneous pompom filaments), and a mixture of LiAlO2+Li2SiO3+LiOH (wherein the Li content is 0.036mol / L) is added for lithium alkali oxidation treatment for 3.5h (pH is 10.3) to obtain an oxidized homogeneous pompom filament liquid. The oxidized homogeneous pompom filament liquid is sent to a blender, 0.35g of lithium acetate is added to the blender, stirred, layered, separated, and the upper layer of suspended matter is taken to obtain a pompom filament hydrogel.

[0061] (3) The pompom filament hydrogel was vacuum dried at 73°C for 6.3 h to obtain pompom filaments, which were then placed in a nitrogen atmosphere (flow rate of 20 mL / min) and sintered at 462°C for 3.1 h. The temperature was then raised to 665°C for a second sintering for 5.5 h. The filaments were then cooled, washed, dried, and ultrasonically crushed to obtain a hard carbon composite negative electrode material.

[0062] Example 3

[0063] The method for preparing the hard carbon composite negative electrode material of this embodiment comprises the following steps:

[0064] (1) Plant pompons were placed in a nitrogen atmosphere and dried at 90°C for 3.5 h. The dried pompons were mixed with 0.13 wt% aminomethyltrimethylsilane solution at a solid-liquid ratio of 4.6 g:100 mL to obtain a homogeneous pompon liquid. The homogeneous pompon liquid was sheared and filamented 6 times (each treatment time was 18 min) to obtain a homogeneous pompon filament liquid (filament diameter <10 μm).

[0065] (2) The homogeneous pompom filament liquid is mixed with LiClO (the amount of LiClO added is 1.6 wt% of the homogeneous pompom filaments), and a mixture of LiAlO2+LiSnO2+LiOH (wherein the Li content is 0.066 mol / L) is added for lithium alkali oxidation treatment for 5.8 h (pH is 9.6) to obtain an oxidized homogeneous pompom filament liquid. The oxidized homogeneous pompom filament liquid is sent to a blender, 0.4 g of lithium acetate is added to the blender, stirred, layered, separated, and the upper layer of suspended matter is taken to obtain a pompom filament hydrogel.

[0066] (3) The pompom filament hydrogel was vacuum dried at 75°C for 6.5 h to obtain pompom filaments, which were then placed in a nitrogen atmosphere (flow rate of 32 mL / min) and sintered at 462°C for 3 h. The temperature was then raised to 823°C for a second sintering for 3.6 h. The filaments were then cooled, washed, dried, and ultrasonically crushed to obtain a hard carbon composite negative electrode material.

[0067] Example 4

[0068] The method for preparing the hard carbon composite negative electrode material of this embodiment comprises the following steps:

[0069] (1) Plant pompons were placed in a nitrogen atmosphere and dried at 85°C for 3.5 h. The dried pompons were mixed with 0.023 wt% aminomethyltrimethylsilane solution at a solid-liquid ratio of 1.2 g:100 mL to obtain a homogeneous pompon liquid. The homogeneous pompon liquid was sheared and filamented 6 times (each treatment time was 16 min) to obtain a homogeneous pompon filament liquid (filament diameter <10 μm).

[0070] (2) The homogeneous pompom filament liquid is mixed with LiClO (the amount of LiClO added is 1.6 wt% of the homogeneous pompom filaments), and a mixture of LiAlO2+Li2SiO3+LiSnO2+LiOH (wherein the Li content is 0.072 mol / L) is added for lithium alkali oxidation treatment for 5 h (pH is 10.2) to obtain an oxidized homogeneous pompom filament liquid. The oxidized homogeneous pompom filament liquid is sent to a blender, 0.4 g of lithium acetate is added to the blender, stirred, layered, separated, and the upper layer of suspended matter is taken to obtain a pompom filament hydrogel.

[0071] (3) The pompom filament hydrogel was vacuum dried at 65°C for 6.5 h to obtain pompom filaments, which were then placed in a nitrogen atmosphere (flow rate of 45 mL / min) and sintered at 462°C for 3 h. The temperature was then raised to 867°C for a second sintering for 5.4 h. The filaments were then cooled, washed, dried, and ultrasonically crushed to obtain a hard carbon composite negative electrode material.

[0072] Comparative Example 1 (no addition of alkali solution for lithium alkali oxidation treatment)

[0073] The preparation method of the hard carbon composite negative electrode material of this comparative example comprises the following steps:

[0074] (1) The plant pompons were placed in a nitrogen atmosphere and dried at 85°C for 3.5 h. The dried pompons were mixed with a 3.5 wt% ethanol solution at a solid-liquid ratio of 4.1 g:100 mL to obtain a homogeneous pompon liquid. The homogeneous pompon liquid was sheared and filamented 6 times (each treatment time was 20 min) to obtain a homogeneous pompon filament liquid (filament diameter <10 μm).

[0075] (2) The homogeneous pompom filament liquid is mixed with LiClO (the amount of LiClO added is 0.86 wt% of the homogeneous pompom filaments) to obtain an oxidized homogeneous pompom filament liquid, and the oxidized homogeneous pompom filament liquid is sent to a blender, 0.35 g of lithium acetate is added to the blender, stirred, layered, separated, and the upper layer of suspended matter is taken to obtain a pompom filament hydrogel.

[0076] (3) The pompom filament hydrogel was vacuum dried at 73°C for 6.3 h to obtain pompom filaments, which were then placed in a nitrogen atmosphere (flow rate of 20 mL / min) and sintered at 462°C for 3.1 h. The temperature was then raised to 665°C for a second sintering for 5.5 h. The filaments were then cooled, washed, dried, and ultrasonically crushed to obtain a hard carbon composite negative electrode material.

[0077] Comparative Example 2 (dispersant is ethanol solution)

[0078] The preparation method of the hard carbon composite negative electrode material of this comparative example comprises the following steps:

[0079] (1) The plant pompons were placed in a nitrogen atmosphere and dried at 95°C for 3.5 h. The dried pompons and 3.5 wt% ethanol solution were mixed at a solid-liquid ratio of 4.1 g:100 mL to obtain a homogeneous pompon liquid. The homogeneous pompon liquid was sheared and filamented 6 times (each treatment time was 18 min) to obtain a homogeneous pompon filament liquid (filament diameter <10 μm).

[0080] (2) The homogeneous pompom filament liquid is mixed with LiClO (the amount of LiClO added is 1.6 wt% of the homogeneous pompom filaments), and a mixture of LiAlO2+LiSnO2+LiOH (wherein the Li content is 0.066 mol / L) is added for lithium alkali oxidation treatment for 5.8 h (pH is 9.6) to obtain an oxidized homogeneous pompom filament liquid. The oxidized homogeneous pompom filament liquid is sent to a blender, 0.35 g of lithium acetate is added to the blender, stirred, layered, separated, and the upper layer of suspended matter is taken to obtain a pompom filament hydrogel.

[0081] (3) The pompom filament hydrogel was vacuum dried at 75°C for 6.5 h to obtain pompom filaments, which were then placed in a nitrogen atmosphere (flow rate of 32 mL / min) and sintered at 462°C for 3 h. The temperature was then raised to 823°C for a second sintering for 3.6 h. The filaments were then cooled, washed, dried, and ultrasonically crushed to obtain a hard carbon composite negative electrode material.

[0082] Application examples:

[0083] The hard carbon composite negative electrode material, acetylene black and polyvinylidene fluoride prepared in Examples 1-4 and Comparative Examples 1-2 were dissolved in N-methylpyrrolidone in a mass ratio of 8:1:1, ground to form a paste active material, and then the paste active material was evenly spread on a Cu foil substrate, placed in a vacuum oven, and dried at 85°C for 8 hours to form an electrode sheet. A lithium sheet was used as a counter electrode, and the electrolyte was 1 mol / L lithium hexafluorophosphate (LiPF6) EC / DMC / DEC (a mixed solution with a mass ratio of 1:1:1). CR2025 button batteries were assembled in a glove box, and electrochemical energy tests were carried out on a LAND battery testing system at a current density of 0.1A / g and 0.01-3V.

[0084] Table 1 is a comparison of the specific surface areas of samples prepared in Examples 1, 2, 3, 4 and Comparative Examples 1 and 2. It is found that the specific surface areas of the samples in the examples are higher than those in the comparative examples.

[0085] Table 1 Specific surface area test data of the embodiments and comparative examples

[0086] sample <![CDATA[Specific surface area (m 2 / g)]]> Example 1 11.02 Example 2 12.17 Example 3 12.87 Example 4 13.63 Comparative Example 1 8.16 Comparative Example 2 10.15

[0087] Electrochemical performance:

[0088] Table 2 compares the electrochemical properties of samples prepared in Examples 1, 2, 3, 4 and Comparative Examples 1 and 2. It is found from the examples that with the increase of nitrogen flow rate during sintering, the specific capacity and first efficiency of the prepared materials are increased. The specific capacity and first efficiency of the examples prepared by the method of the present invention are higher than those of the comparative examples.

[0089] Table 2 Electrochemical performance test data of the embodiments and comparative examples

[0090] sample <![CDATA[Specific discharge capacity upon de-lithiation (mAh g -1 )]]> First effect (%) Example 1 330.5 71.75 Example 2 332.8 73.19 Example 3 340.7 75.29 Example 4 331.6 72.19 Comparative Example 1 300.1 50.12 Comparative Example 2 308.2 61.69

[0091] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A hard carbon composite negative electrode material, characterized in that: The invention comprises the following raw materials: plant pompoms, an oxidant, a lithium source, a dispersant and a lithium salt containing a carboxyl group; the lithium source is at least one of LiAlO2, Li2SiO3 and LiSnO2; The dispersant is one of aminomethyltrimethylsilane solution and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane; The oxidant is LiClO; The method for preparing the hard carbon composite negative electrode material comprises the following steps: (1) mixing plant pompoms and a dispersant, and then homogenizing to obtain a homogenous pompom filament liquid; (2) mixing the homogeneous pompom filament liquid, an oxidant, a lithium source and an alkali solution, performing a lithium-alkali oxidation treatment, adding a carboxyl-containing lithium salt, performing a grafting reaction, stirring and layering, separating, and taking the upper suspended matter to obtain a pompom filament hydrogel; (3) Drying the pompom filament hydrogel, performing a primary sintering, raising the temperature, and performing a secondary sintering to obtain the hard carbon composite negative electrode material.

2. The hard carbon composite negative electrode material according to claim 1, characterized in that The carboxyl-containing lithium salt is lithium acetate.

3. The hard carbon composite negative electrode material according to claim 1, characterized in that: The plant pompom is at least one of gentiana scabra, dandelion, rudbeckia oleracea or ageratum.

4. The hard carbon composite negative electrode material according to claim 1, characterized in that: The specific surface area of ​​the hard carbon composite negative electrode material is 10-15m 2 / g.

5. The hard carbon composite negative electrode material according to claim 1, characterized in that: The lithium removal specific capacity of the hard carbon composite negative electrode material is 330.5-340 mAh·g -1 ; The initial efficacy is 71-76%.

6. The method for preparing the hard carbon composite negative electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing plant pompoms and a dispersant, and then homogenizing to obtain a homogenous pompom filament liquid; (2) mixing the homogeneous pompom filament liquid, an oxidant, a lithium source and an alkali solution, performing a lithium-alkali oxidation treatment, adding a carboxyl-containing lithium salt, performing a grafting reaction, stirring and layering, separating, and taking the upper suspended matter to obtain a pompom filament hydrogel; (3) Drying the pompom filament hydrogel, performing a primary sintering, raising the temperature, and performing a secondary sintering to obtain the hard carbon composite negative electrode material.

7. The preparation method according to claim 6, characterized in that: In step (2), the alkaline solution is LiOH solution; and the carboxyl-containing lithium salt is lithium acetate.

8. The preparation method according to claim 6, characterized in that: In step (3), the temperature of the primary sintering is 400-500° C., and the time of the primary sintering is 2-6 hours; the temperature of the secondary sintering is 500-1200° C., and the time of the secondary sintering is 2-6 hours.

9. Use of the hard carbon composite negative electrode material according to any one of claims 1 to 5 in the preparation of batteries, catalysts or supercapacitors.

Citation Information

Patent Citations

  • Composite anode material for lithium ion battery, preparation method of composite anode material and lithium ion battery

    CN106505199A

  • Method for preparing graphitized hierarchical porous carbon material by oxidant redox

    CN108928819A

  • Hard carbon negative electrode composite material and preparation method and application thereof

    CN113184828A